Images of the unimaginable: photography and the (re)presentation of the event - Sergio Roncallo; Juan Carlos Arias (Discursos Fotográficos, 2013)
We seem to live in a time of omnipresent images. Guy Debord’s diagnosis about the becoming image of reality pronounced in the late 1960s still seems to be relevant to describe our time. We have reached the point when it is not surprising to have images of the extraordinary but not having them. The connection between extraordinary events and images seems natural today. However, it could be still legitimate to ask what can images do regarding those events? What can photography do when facing the unimaginable? In this text, we would like to present three cases that could serve, and actually have been used, to reply this inquiry about the possible relation between photography and the event.